Wicked Problems in Public Policy Understanding and Responding to Complex Challenges - Head, Brian W. (Springer International Publishing : Imprint: Palgrave Macmillan, 2022)
"The concept of wicked problems has become very commonly used, and abused, in contemporary studies of public policy. While expressing some appropriate skepticism about the concept, Brian Head uses the idea to analyse the numerous difficult problems facing governments in the 21st century." ---B. Guy Peters, Maurice Falk Professor of American Government, University of Pittsburgh, USA "Rich with empirical detail, this book looks set to become the definitive work on wicked issues and what to do about them." ---Claire A. Dunlop, Professor of Politics, University of Exeter, UK "This book provides a concise introduction to the concept and management of "wicked" problems: the kind of poorly-structured, intractable policy problems with unknown solutions with which policy-makers, unfortunately, must engage on a frequent basis." ---Michael Howlett, Burnaby Mountain Professor and Canada Research Chair, Simon Fraser University, Canada This is an open access book. This book offers the first overview of the 'wicked problems' literature, often seen as complex, open-ended, and intractable, with both the nature of the 'problem' and the preferred 'solution' being strongly contested. It contextualises the debate using a wide range of relevant policy examples, explaining why these issues attract so much attention. There is an increasing interest in the conceptual and practical aspects of how 'wicked problems' are identified, understood and managed by policy practitioners. The standard public management responses to complexity and uncertainty (including traditional regulation and market-based solutions) are insufficient. Leaders often advocate and implement ideological 'quick fixes', but integrative and inclusive responses are increasingly being utilised to recognise the multiple interests and complex causes of these problems. This book uses examples from a wide range of social, economic and environmental fields in order to develop new insights about better solutions, and thus gain broad stakeholder acceptance for shared strategies for tackling 'wicked problems'. Brian Head is Professor of Public Policy at the University of Queensland, Australia. He is the editor or co-author of 12 books and over 100 academic articles on public management, governance, social issues and environmental policy. .